The Nonlinear Relationship Between Inflation and Economic Growth A Macroeconomic Investigation - Khaira Rizka Pane; Voni Uviani; Nuraini Asriati; Syamsuri (PT SOLUSI EDUKASI BERDIKARI, 2026)
Inflation is a key indicator of a country’s economic stability and is closely linked to economic growth. However, the relationship between inflation and economic growth is not always linear. This study aims to analyze the nonlinear relationship between inflation and economic growth and to identify the threshold level of inflation that affects economic growth. The method used in this study is a literature review, analyzing various empirical studies that discuss the relationship between inflation and economic growth in various countries. The results of the study indicate that low to moderate levels of inflation can have a positive impact on economic growth as they can stimulate production and investment activities. However, when inflation rises beyond a certain threshold, its impact on economic growth becomes negative due to increased economic uncertainty, a decline in purchasing power, and a reduction in investment activity. Therefore, inflation stability is a critical factor in maintaining sustainable economic growth. This study implies that effective monetary policy must maintain inflation at an optimal level to support economic stability and long-term growth.